Modified dual-injection lumbar erector spine plane (ESP) block for opioid-free anesthesia in multilevel lumbar laminectomy - Kline, Jonathan; Chin, Ki Jinn (Korean journal of anesthesiology, 2019)
KCI Citation Count: 2